SEVERE BILATERAL RETINAL VASCULAR OCCLUSION AS FIRST PRESENTATION OF SYSTEMIC LUPUS ERYTHEMATOSUS AND ANTIPHOSPHOLIPID SYNDROME. (2017) - Storey, Philip; Ter-Zakarian, Anna; Rao, Narsing; Rodger, Damien
Abstract : Purpose: To describe a patient with undiagnosed systemic lupus erythematosus and secondary antiphospholipid syndrome presenting with bilateral severe retinal vaso-occlusion on first presentation. Methods: Retrospective case report. A 42-year-old Hispanic female with no medical history presented with 2 weeks of bilateral decreased vision. Results: At initial presentation, the patient's best-corrected visual acuity was 2 ft/200 and 20/400 in the right and left eyes, respectively. Dilated fundus examination revealed diffuse, confluent cotton-wool spots, and severe vascular occlusions in both eyes. Fluorescein angiography confirmed that the patient had both arterial and venous vascular occlusions and retinal vasculitis. A thorough work-up revealed that the patient had systemic lupus erythematosus and APS with positive antibodies to anticardiolipin, beta-2-glycoprotein, and lupus anticoagulant. The patient was treated with steroids, immunosuppression agents, anticoagulation, and extensive panretinal photocoagulation. One month later, best-corrected visual acuity had improved to 20/200 and 20/40, the vasculitis had substantially improved, and no neovascularization was present. Conclusion: Severe retinal vaso-occlusion may be the first presenting signs for patients with systemic lupus erythematosus and APS. Abstract : A 42-year-old Hispanic female with no medical history presented with 2 weeks of bilateral decreased vision and severe bilateral venous and arterial occlusive disease. A complete work-up revealed the patient had undiagnosed systemic lupus erythematosus and secondary antiphospholipid syndrome with positive antibodies to anticardiolipin, beta-2-glycoprotein, and lupus anticoagulant.